Una poetica per l'inclusione della disabilità - William Grandi (Firenze University Press, 2012)
The article investigates recent Children's Literature, in order to find out metaphors and references about disabled people. This research shows that Children's Literature can enable children and grown-up people not only to know disabilities, but also to start up social integration of disabled person. Ultimately Children's Literature can be an effective tool to know and help disabled childhood.